PENEGAKAN HUKUM OLEH PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) PADANG TERHADAP PANGAN OLAHAN TANPA IZIN EDAR (Studi Kasus: di Wilayah Hukum BBPOM Kota Padang) - Febrian Akhirama Saputra; Najmi Najmi; Aria Zurnetti (UNES Law Review, 2023)
Processed food is everything that originates from agricultural, plantation, forestry, fishery, water and water products, either processed or not processed, which are intended as food or drink for human consumption, including processed food additives, processed food raw materials, and processed food ingredients. other products that are used in the process of preparing, processing and/or making food or drink, in order to maintain the safety of processed food, this is where the role of the government through the Food and Drug Supervisory Agency (BPOM) is needed to oversee drug and food distribution. The ineffectiveness of supervision and law enforcement on the distribution of drugs and food is due to the poor legal culture of society which is one of the factors causing the high circulation of processed food without a distribution permit, besides that it is also influenced by the weakness of substance and legal structure. Efforts to tackle crime with criminal law are essentially part of law enforcement efforts. The issue raised in this study is how is law enforcement by Civil Servant Investigators (PPNS) Padang Food and Drug Supervisory Agency (BBPOM) against the circulation of processed food without a distribution permit and what are the obstacles and obstacles. The research used is a sociological juridical approach which is analytically descriptive in nature, namely analyzing the link between applicable laws and regulations and legal theories and implementation practices related to the research object which then produces several conclusions. In carrying out surveillance of processed food circulating in the community, BBPOM still often finds processed food without a distribution permit that does not meet processed food standards. In carrying out law enforcement, BBPOM already has several mechanisms in accordance with statutory regulations where these rules have a juridical aspect that can guarantee certainty that the law functions as a rule that must be obeyed. In fact, the investigation and supervision carried out by BBPOM has not guaranteed legal certainty, because existing regulations are not adhered to and the constraints faced are the lack of availability of human resources and the weak authority of BBPOM in taking action against processed food without a distribution permit.